PREVALENCE AND DIAGNOSIS OF SEXUALLY TRANSMITTED PATHOGENS IN A SAMPLE OF IRAQI WOMEN: A MOLECULAR STUDY (Iraqi Journal of Medical Sciences, 2018)
Background: Sexually transmitted infections (STI), also referred to as sexually transmitted diseases (STD) and venereal diseases (VD), are infections that are commonly spread by sex, especially vaginal intercourse, anal sex and oral sex. Most STIs initially do not cause symptoms. This results in a greater risk of passing the disease on to others. Symptoms and signs of disease may include: vaginal discharge, penile discharge, ulcers on or around the genitals, and pelvic pain.Objective: To detect the two microorganisms (Gardnerella vaginitis (G. vaginalis) and Trichomonas vaginalis (T. vaginalis)) in the same sample taken from women with genital tract infection by microbiological and molecular methods and to investigate the contributions of some socioeconomic factors and clinical features.Methods: Two hundred samples were collected from females attending the Gynecology out-patient department in the Al-Imamein Al-Kadhimein Medical City and Baghdad Teaching Hospital during the period from May 2014 to April 2015. Based on availability of full clinical information about each patient, high vaginal swabs were taken from females at different ages (15-54 years) representing patients group complaining of abnormal vaginal discharge with or without other symptoms, questionnaire was applied. The two diseases associated with vaginal infection include G. vaginalis and T. vaginalis. Each of the vaginal swabs collected was examined microscopically, whilst the remaining was preserved at -20 °C for DNA extracts were analyzed with the real-time poly meres chain reaction (RT-PCR). Results: In RT-PCR, the rate of infection was 120 (60%) G. vaginalis, and 34 (17%) T. vaginalis. Highest rate of infection in women with G. vaginalis was among age group (15-24) years and (25-34) years 38.3%, 35.0% respectively, the lowest rate was among age group (45-54) years 8.3 %. In T. vaginalis, the highest rate of infection was among age group (15-24) years 61.7 %, the lowest was among age group (35-44) years 8.8 % and on infection in age 45-54years.Conclusion: The commonest genital tract infections among women were G. vaginalis and T. vaginalis. Molecular methods are considered the gold standard for diagnosis, given the excellent sensitivities and specificities in diagnosis. Presence of clinical symptoms helps and lab diagnosis of infection. Vaginal swab samples showed that most common co-infection is between G. vaginalis cases and T. vaginalis.Keywords: Sexually transmitted infections, Gardnerella vaginalis, Trichomonas vaginalis, molecular studyCitation: Ali MK, Hathal HD, Almoayed HA. Prevalence and Diagnosis of sexually Transmitted Pathogens in A Sample of Iraqi Women: A Molecular Study. Iraqi JMS. 2017; Vol. 15(4): 364-376. doi: 10.22578/IJMS.15.4.7